2014
DOI: 10.1016/j.phanu.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Detection and treatment of long-chain omega-3 fatty acid deficiency in adolescents with SSRI-resistant major depressive disorder

Abstract: Residual depressive symptoms are commonly observed in adolescents with major depressive disorder (MDD) following treatment with selective serotonin reuptake inhibitors (SSRIs). This study combined a case-control analysis and an open-label fish oil (FO) trial to investigate the relationship between long-chain omega-3 (LCn-3) fatty acid status and residual depressive symptoms in SSRI-resistant adolescent MDD patients. Baseline erythrocyte docosahexaenoic acid (DHA)(-28%, p=0.0003), but not eicosapentaenoic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
75
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 57 publications
7
75
0
1
Order By: Relevance
“…In addition, studies by Ferraz et al ( 85 ) and DeMar et al ( 86 ) indicated that feeding male rats diets supplemented with fi sh oil or ␣ -linolenic acid, respectively, after weaning (P21) into adulthood for 6 months decreased data, only trace levels of EPA are found in the brain where upon entry it is rapidly ␤ -oxidized and metabolized ( 97,98 ). Furthermore, erythrocyte DHA, but not EPA, content was shown to be lower in SSRI-resistant depressed adolescents compared with healthy counterparts ( 29 ). Given that DHA, but not EPA, is highly enriched in neural tissue and is essential for brain development, it may play a critical role in the developmental factors that shape the etiology of adolescent depression, a supposition in alignment with the results of our study.…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies by Ferraz et al ( 85 ) and DeMar et al ( 86 ) indicated that feeding male rats diets supplemented with fi sh oil or ␣ -linolenic acid, respectively, after weaning (P21) into adulthood for 6 months decreased data, only trace levels of EPA are found in the brain where upon entry it is rapidly ␤ -oxidized and metabolized ( 97,98 ). Furthermore, erythrocyte DHA, but not EPA, content was shown to be lower in SSRI-resistant depressed adolescents compared with healthy counterparts ( 29 ). Given that DHA, but not EPA, is highly enriched in neural tissue and is essential for brain development, it may play a critical role in the developmental factors that shape the etiology of adolescent depression, a supposition in alignment with the results of our study.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Indeed, DHA defi ciency throughout development leads to decreased DHA levels in neural tissue and is associated with defi cits in psychomotor development ( 21 ), problem solving ( 22 ), reading skills ( 23 ), visual acuity ( 24 ), and attention ( 25 ). Furthermore, emerging clinical data support a link between suffi cient DHA intake with a reduction in the incidence and/or symptomatic relief of adolescent depression ( 5,(26)(27)(28)(29), and there exists an abundance of clinical evidence supporting a positive role for the omega-3 PUFA EPA in the treatment of adult depression ( 30 ). However, the studies examining the importance of DHA, in particular, are limited in scope and interpretation, and no longitudinal studies have been reported to date.…”
mentioning
confidence: 99%
“…For example, in an adolescent population with SSRI-resistant major depressive disorder, erythrocyte DHA, but not EPA, was significantly lower in patients compared with healthy controls (McNamara et al, 2014). In a study by Pottala et al, (2012) levels of red blood cell EPA+DHA were lower in depressed adolescents compared to non-depressed adolescent controls.…”
Section: Omega 3 Polyunsaturated Fatty Acids and Depressionmentioning
confidence: 93%
“…Symptom remission was observed in 40% of patients in the low-dose group and 100% of patients in the high-dose group. Adverse events included mild-to-moderate severity of headache and gastrointestinal symptoms but this did not lead to a discontinuation in treatment (McNamara et al, 2014).…”
Section: Omega-3 Pufas For the Treatment Of Paediatric Depressionmentioning
confidence: 99%
See 1 more Smart Citation